Penggunaan Coaching Model GROW-ME untuk Meningkatkan Kompetensi Guru Bahasa Inggris dalam Menyusun Asesmen Pembelajaran - Kristina Dian Insani; Hery Winoto Tj; Takim Andriono (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Conducting learning assessments is a teacher's activity aimed at collecting evidence of learning objective achievement. Teacher competence plays a crucial role in formulating learning assessments, ensuring they go beyond written tests alone. An action research was conducted with the objective of evaluating the use of the GROW-ME Coaching Model to enhance English teachers' competence in developing learning assessments. The research was carried out in two cycles, each involving four stages: Planning, Implementation, Observation, and Reflection. Coaching was conducted during the Implementation stage following the GROW-ME model, including Goal, Reality, Option, Will/What Next, Monitoring, and Evaluation. The research subjects were three English teachers at Masa Depan Cerah Christian Elementary School. The results of the research indicate that the use of the GROW-ME Coaching Model is effective in improving teacher competence in crafting learning assessments. By the end of the second cycle, two subjects achieved scores of 91 (Excellent), while one subject scored 80 (Good). Thus, all three subjects met the success criteria with a minimum score in the Good category.